The Influence Of Financial Literacy, Social Environment And Self-Control On Consumptive Behavior With Buying Interest As A Mediating Variable - Rosyada, Irfatur; Rusdarti; Pujiati, Amin (Universitas Negeri Semarang, 2025)
The phenomenon of consumerism has spread in society, including among teenagers who tend to show consumptive behavior due to a preference for novelty and the process of finding self-identity. Therefore, students as a group of highly educated teenagers need to develop self-control skills in consuming to avoid uncontrolled consumptive behavior. The purpose of this study is to analyze consumptive behaviors including financial literacy, social environment, self-control and buying interest. The data collection technique used questionnaires, while the data analysis technique used percentage descriptive analysis, inferential statistics, and multiple linear regression analysis. The results of the study show that financial literacy, social environment, and self-control have a positive effect on consumptive behavior. And the buying interest variable has been proven to play a mediator role in consumptive behavior. The advice given is for students to learn to increase awareness in responding to discounts, understand the financial landscape, pay attention to consumer reviews and testimonials, develop self-control, and foster rational buying interest. This study also advises future researchers to develop broader research statements and variables to strengthen the relevance of the research results and theories used.